Studi modeling dan mapping inundasi tsunami menggunakan software Delft3D studi kasus Pantai Labuan Jukung Lampung - M. Gilang Indra Mardika; Mashuri; Dandi Rahman Hakim (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
To begin with, one of the valuable beaches at Pesisir Tengah Krui District is Labuhan Jukung Beach that directly encounters the Indian Ocean and is crossed by tectonic plates. The current position could consequence a tsunami disaster and cause loss and damage to the area at any time soon. In addition, no hazard map released by the National Center for Volcanology and Disaster Mitigation in the study location is one of the shortcomings of tsunami-prone areas in the West Coast tourist area. Tsunami wave propagation model establishment is a monumentally vital step in tsunami mitigation to pinpoint areas which are vulnerable to tsunami disasters and maximize the damage control. One way or another is by utilizing Delft3D 4.04.01 software according to wave propagation simulation scenario analysis. The input for modeling adopts historical tsunami height data which has similar characteristics to the case study location points, simultaneously 3.6 meter, 8 meter and 15 meter. The outcome wave height of 3.6 meter takes within 36 minutes to reach the coast and it does not cause inundation, meanwhile the outcome of waves height of 8 meter and 15 meter are accomplishing a tsunami inundation on land which takes 33 - 35 minutes to approach the coast. The data used in these scenarios demands the model accuracy requirements of modeling validation by inspecting the wavelengths formed in shallow water. Based on all of these scenario modeling results, the maximum propagation scenario for an 8 meter wave height on land is 330 meter, on the other hand for a 15 meter wave height is 450 meter from the coastline.